Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Bagian Produksi pada Perusahaan PT. Xyz - Arief, Basyirudin; Romi, Mochamad Vrans (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze the influence of work motivation and work discipline on the performance of production department employees at PT. XYZ. The study employs a quantitative approach using descriptive and associative methods. The study population consisted of 39 employees, all of whom were included in the sample through saturation sampling. Data were collected through observation, documentation, and questionnaires, then analyzed using multiple linear regression with the aid of SPSS version 27. The results show that work motivation has a positive and significant effect on employee performance, with a t-value of 4.314 and a significance level of 0.001. Work discipline also has a positive and significant effect on employee performance, with a t-value of 3.845 and a significance level of 0.001. Simultaneously, work motivation and work discipline have a positive and significant effect on employee performance, with an F-value of 15.552 and a significance level of 0.001. The coefficient of determination (R²) of 0.464 indicates that these two variables account for 46.4% of the variation in employee performance, while 53.6% is influenced by other factors outside the scope of this study. These findings suggest that consistently improving work motivation and work discipline can enhance the performance of production department employees.